2006
DOI: 10.1016/s0899-3467(07)60143-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of active release technique on carpal tunnel patients: A pilot study

Abstract: (J Chiropr Med 2006;5:119-122)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Electromyographic analyses had also been used to quantify the effectiveness of some chiropractic techniques in treating carpal tunnel syndrome. 44,45 For instance, George et al 45 tried to quantify active release technique as a conservative management strategy for carpal tunnel syndrome patients. Results supported the need for further clinical trials with larger samples, and our SMG protocols show the potential to help with this kind of setting to obtain more information.…”
Section: Discussionmentioning
confidence: 99%
“…Electromyographic analyses had also been used to quantify the effectiveness of some chiropractic techniques in treating carpal tunnel syndrome. 44,45 For instance, George et al 45 tried to quantify active release technique as a conservative management strategy for carpal tunnel syndrome patients. Results supported the need for further clinical trials with larger samples, and our SMG protocols show the potential to help with this kind of setting to obtain more information.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous patient and physician testimonials to account for the success of this type of therapy, there is minimal scientific research available that investigates this popular technique. However, George et al 14 found that ART provided significant improvements in symptom severity and functional status in a small sample of carpal tunnel syndrome patients.…”
Section: Discussionmentioning
confidence: 97%
“…A 2-week, 5-subject case series suggested that ART reduced self-reported symptoms but did not alter muscle activation (electromyography) in patients with carpal tunnel syndrome. 11 One study of asymptomatic subjects found that hamstring flexibility improved immediately following ART treatment. 12 One noncontrolled study of symptomatic patients demonstrated reduced pain pressure thresholds in strained groin muscles immediately following ART treatment.…”
Section: Discussionmentioning
confidence: 99%